Ultrasound of the hand is sufficient to detect subclinical inflammation in rheumatoid arthritis remission: a post hoc longitudinal study - Hilde Berner Hammer; Tore K. Kvien; Lene Terslev (Arthritis Research & Therapy, 2017)
Abstract Background Ultrasound (US) is a sensitive method for detecting joint/tendon inflammation in patients with rheumatoid arthritis (RA). Subclinical inflammation is often found in patients with RA in composite score remission. The purpose of the present study was to explore whether US of only the hands is sufficient to identify subclinical inflammation in patients with established RA in clinical remission. Methods A total of 209 patients with established RA (81% women, mean [SD] age 53.3 (13.2) years, disease duration 10.0 [8.8] years) were examined when initiating biologic disease-modifying anti-rheumatic drugs (bDMARDs) and after 6 months (184 patients) and 12 months (152 patients) of follow-up. They were assessed by US (greyscale [GS] and power Doppler [PD] of 36 joints and 4 tendons, scored 0–3) as well as clinical and laboratory examinations, and different disease activity composite scores were calculated. The presence of US synovitis (GS score ≥ 2, PD score ≥ 1 [PD1] and score ≥ 2 [PD2]) in composite score remission was explored. Results Remission at 6 and 12 months was achieved in 74 and 59 patients, respectively, for Disease Activity Score based on 28 joints (DAS28); in 37 and 38 patients, respectively, for Clinical Disease Activity Index; in 42 and 42 patients, respectively, for Simplified Disease Activity Index; and in 38 and 35 patients, respectively, for Boolean remission. The percentages of patients in DAS28 remission at 6 months with synovitis in hands/other regions were 73.0%/64.9% for GS, 64.9%/41.9% for PD1 and 32.4%/20.3% for PD2; at 12 months, the corresponding percentages were 61.0%/64.4% for GS, 62.7%/39.0% for PD1 and 44.1%/15.3% for PD2, respectively. PD activity was more often present in the hands (p < 0.001). In patients in various composite scores of remission, US only of the hands identified ≥ 90% of the patients having PD activity in any of the assessed joints/tendons. Conclusions A high percentage of patients had US synovitis despite being in clinical remission. US examination performed only of the hands captured ≥ 90% of patients with subclinical inflammation and could be feasible for assessing bDMARD-treated patients with RA in remission. Trial registration Australian New Zealand Clinical Trials Registry, ACTRN12610000284066 . Registered on 8 April 2010.